ALTERATIONS IN THE MOUSE VIRULENCE OF SALMONELLA TYPHIMURIUM BY GENETIC RECOMBINATION - Krishnapillai, V. (1964)
Krishnapillai, V. (Walter Reed Army Institute of Research, Washington, D.C.), and L. S. Baron. Alterations in the mouse virulence of Salmonella typhimurium by genetic recombination. J. Bacteriol. 87:598–605. 1964.—The genetic basis of mouse virulence was investigated with an avirulent strain of Salmonella abony as chromosomal donor and a virulent strain of S. typhimurium as recipient in recombination experiments. In these genetic crosses, the transfer of partial avirulence was found to segregate among the hybrids that were examined. At least two determinants controlling avirulence were depicted to account for the partial avirulence of the hybrids. One of these determinants is indicated as being in the region of the locus for streptomycin sensitivity or resistance, and the other was adjacent to the locus for inositol utilization. Moreover, both determinants were essential for the phenotypic expression of complete avirulence in a hybrid. This was established by the results of experiments in which an initial, partially avirulent hybrid was backcrossed with the S. abony donor so that it further received the additional determinant.